The Oxford Handbook of the Italian Economy Since Unification 2013
DOI: 10.1093/oxfordhb/9780199936694.013.0011
|View full text |Cite
|
Sign up to set email alerts
|

Democratization and Civic Capital

Abstract: We document a sharp reversal in electoral participation between the North and the South of Italy after the 1912 enfranchisement which extended voting rights from a limited élite to (almost) all adult males. When voting was restricted to the élite, electoral turnout was higher in the South but falls significantly below that in the North after the enfranchisement. Furthermore the new gap is never bridged over the following century and participation remains lower in the South despite the enrichment of democratic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 125 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…On the critical role played by trust in economic performance, see Arrow (1972) and Alesina and Giuliano (2015) for a recent survey. On the persistent character of social capital, see Guiso, Sapienza, and Zingales (2008), Guiso and Pinotti (2012) and Bisin and Verdier (2010). For a discussion about the similarities between informal institutions and social capital, see Knowles (2006).…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…On the critical role played by trust in economic performance, see Arrow (1972) and Alesina and Giuliano (2015) for a recent survey. On the persistent character of social capital, see Guiso, Sapienza, and Zingales (2008), Guiso and Pinotti (2012) and Bisin and Verdier (2010). For a discussion about the similarities between informal institutions and social capital, see Knowles (2006).…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…The victory of the ruling classes in the suppression of the peasant revolts in Southern Italy also influenced Italy's poor economic performance (Sereni, ). As a result, the Risorgimento “remained essentially an element between the Savoy monarchy and the urban high class, whereas large segments of the peasant population were, at best sceptical about or even fiercely against, the process of unification” (Guiso & Pinotti, , p. 309).…”
Section: Rural Troubles Modernization and Global Changes In The Ottmentioning
confidence: 99%
“…18 Finally, Guiso and Pinotti have also shown that social capital levels differed to a large extent across Italy's regions prior to WWI, by using a quasi-natural experiment based on the extension of franchise in 1912. 19 Although these different contributions have identified large regional disparities in social capital on the eve of the 20 th century, the hypothesis on the importance of social capital for regional divergence before the Great War remains untested, mainly because of the lack of data and measurement problems. This work aims to fill the gap, by connecting social-capital estimates at provincial level with the growth of industry across areas of the country between 1871 and 1911.…”
Section: Literature Review: Social Capital and Italy's Regional Devel...mentioning
confidence: 99%